A triple-targeting “nano-brake” remodeling the impaired immune microenvironment in skin lesions for psoriasis treatment - Ruijie Chen; Baiqun Duan; Shize Li; Yixuan Zhu; Zihao Huang; Dingchao Shen; Zhanzheng Ye; Yuqi Yan; Chenyu Qiu; Haoxiong Guan; Yinsha Yao; Jie Dong; et al. (Materials Today Bio)
Psoriasis, a prevalent immune-mediated chronic inflammatory skin ailment, has been linked to heightened oxidative stress and compromised immune tolerance. Immune checkpoint pathways, particularly the programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) signaling axis, are instrumental in establishing and sustaining self-tolerance and regulating immune responses. Augmenting PD-1/PD-L1 interaction holds promise for curtailing the proliferation and activation of infiltrating T cells and curbing the release of inflammatory cytokines, thereby mitigating psoriasis induced by impaired immune tolerance. Consequently, neutralizing the surplus reactive oxygen species (ROS) in the affected skin and revitalizing local immune tolerance could represent a beneficial approach to psoriasis treatment. In light of these insights, this study introduced a bilirubin-based nanoparticle cloaked in IFN-γ-stimulated macrophage membrane (designated as IMφm@GBn or ''nano-brake''). Treatment with IFN-γ conferred the macrophage membrane with heightened expression of pro-inflammatory cytokine receptor and PD-L1. As a result, the engineered IMφm@GBn not only scavenged excessive ROS in psoriatic lesions but crucially also absorbed a wide spectrum of pro-inflammatory cytokines. Furthermore, it inhibited the proliferation and activation of infiltrating T cells through augmented PD-1/PD-L1 interactions, thereby rebalancing the Th17/Treg ratio. In an in vivo psoriasis mouse model, the ''nano-brake'' was locally and accurately delivered to the dermis via microneedle, orchestrating the immune microenvironment of psoriasis and mitigating autoimmune damage linked to impaired immune tolerance. This approach significantly enhanced the therapeutic efficacy in ameliorating psoriasis-associated symptoms. This study sets an illuminating precedent for cell membrane-based biomimetic nano-formulations, holding broad implications for psoriasis treatment through multi-pronged immunomodulation.